Prediction Competition Result of Indonesian Football Club with C.45 Algorithm - Subiksa, Gde Brahupadhya; Pradnya Pramita, Made Dinda; Saputra, Komang Oka (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Indonesia is a country that is very fond of soccer sport, according to Gojek-Traveloka League data there are an average of 13,423 spectators watching every game. With a sizeable audience and a fairly regular schedule of matches by clubs and leagues in Indonesia. It makes predictions interesting because it will provide an overview and direction of support for the competing club. In some studies relating to predictions and decisions recommending the use of excessive C4.5 methods or algorithms, such as the C4.5 algorithm can produce decision trees that are easy to interpret, have an acceptable level of accuracy, efficient in dealing with discrete type attributes and can handle attribute of discrete and numeric type. So based on the explanation, this research will discuss about the prediction of Indonesian football club match using C4.5 method based on game history that has been done before. The purpose of this research is to know how far C4.5 method can be applied in predicting soccer match. The results of this study indicate that the C4.5 algorithm can be implemented in predictions of the results of the game proved with a fairly good accuracy of 63.04%.